Age differences in the influence of self-esteem and emotional regulation on memory - Doron, Yaffa; Anaki, David (Frontiers in Psychology, 2024)
Emotion regulation (ER) comprises the processes that recognize, monitor, evaluate, and modify emotional reactions. Although ER refers to events that stem from internal or external situations, few studies have examined the effect of intrinsic emotional states on ER processes deployed on external stimuli. The present research investigated, in old-vs. young adults, the influence of state self-esteem (internal condition) in employing ER strategies while implicitly memorizing negative-valence pictures (external condition). State self-esteem was manipulated by giving random feedback (positive/negative) to a demanding cognitive task. Participants then saw 20 photographs and were asked to reappraise half of them and distract themselves from the other half. They were given a recognition task following a short delay with 20 old photographs and 20 new ones. Results indicated that young people with high selfesteem remembered the reappraised pictures better than the distracted ones. In the low self-esteem state, young adults remembered the distracted photographs better than the reappraised ones. In contrast, low self-esteem resulted in better recognition among old adults regardless of the regulation strategy. Thus, only among young participants did emotion regulation strategies moderate the effect of self-esteem on memory for negative emotional images. These findings highlight the intricate interplay between different ER strategies and their relative importance across various stages of life.